Development of a smart thyristor valve for HVDC transmission - Gianluca, De Bonis (2019)
In HVDC transmission schemes, two converters are needed: a rectifier at the sending point and an inverter at the receiving point. Depending on voltage and current ratings, many types of converters can be chosen. For voltages of hundreds of kV and currents of a few kA, thyristor converters are one of the best solutions, because they have the highest voltage withstanding capability and the highest efficiency, compared to other power semiconductor devices. A thyristor converter is realized by many valve sections, whose volume is approximately occupied for only the 10% by thyristors and for the 10% by the gate drivers. The remaining 80% is taken by passive auxiliary circuits, needed to protect thyristors during turn-on and turn-off commutations. Aim of this project is the reduction of the auxiliary circuit size, to reduce costs, volume and weight of the overall valve, through the investigation of active, instead of passive solutions. The project starts from a theoretical investigation, including literature review, and proceeds with simulations of the proposed control methods. The last step is an experimental work, using a reduced scale test circuit. The proposed active control circuits are successfully validated. Experimental results match simulation results, therefore, the investigated active configurations can be used for improving the actual thyristor valves. Future directions are high voltage experimental tests and the realisation of a real scale prototype, to verify the effective costs, volume and weight reduction of the updated valve, compared to the current state of the art.